2021
DOI: 10.1001/jamasurg.2021.3005
|View full text |Cite
|
Sign up to set email alerts
|

Trainee Sex and Accreditation Council for Graduate Medical Education Milestone Assessments During General Surgery Residency

Abstract: In evaluating the effectiveness of general surgery (GS) training, an unbiased assessment of the progression of residents with attention to individual learner factors is imperative.OBJECTIVE To evaluate the role of trainee sex in milestone achievement over the course of GS residency using national data from the Accreditation Council for Graduate Medical Education (ACGME). DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study evaluated female and male GS residents enrolled in ACGME-accredited programs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
(74 reference statements)
1
20
2
Order By: Relevance
“…It is also possible that disparities and potential biases related to gender and race and ethnicity might have affected Milestones ratings and/or patient complaints . In the present study, we found no difference in the proportion rated as below target for the Milestones by gender and no difference in the proportion with patient complaints by gender.…”
Section: Discussioncontrasting
confidence: 66%
“…It is also possible that disparities and potential biases related to gender and race and ethnicity might have affected Milestones ratings and/or patient complaints . In the present study, we found no difference in the proportion rated as below target for the Milestones by gender and no difference in the proportion with patient complaints by gender.…”
Section: Discussioncontrasting
confidence: 66%
“…Any qualitative, global assessment without objective metrics of success is inherently incomplete and may additionally be fraught with racial, gender, and cultural biases. [28][29][30] To the extent that trainees, program directors, and ACGME must, at least in part, rely on objective metrics such as case logs, we believe this revised case log system to be a significant leap forward from its predecessor.…”
Section: Discussionmentioning
confidence: 99%
“…It requires medical students to possess advanced medical knowledge and high standard operation skills, often being one of the most difficult clinical trainings for medical students [ 6 ]. Gastrointestinal surgery training helps improve other essential skills for medical students, such as clinical thinking ability, and lays a foundation for further study of other specialties [ 7 ].…”
Section: Introductionmentioning
confidence: 99%